Between Job and Homo Sovieticus: Sergei Bondarchuk’s Fate of a Man as a Masterpiece of Propaganda Cinema - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2023)
The subject of this article is a famous Soviet war-film, Fate of a Man (1959), directed by Sergey Bondarchuk and based on the short-story written by the Nobel Price winner, Mikhail Sholokhov. The proposed analysis aims at uncovering an essential but hidden context of Bondarchuk’s vision of 20th century traumatic human experiences: the Old Testament Book of Job. Focused onthe subtle meanings being created between gestures, words, sounds and pictures, the author tries to show the presence as well as the function of biblical images in this ‘most Soviet of the Soviet movies’. It would be useless to seek such dimensions in the literary version of the same story. Owing to his audiovisual sensibility, Bondarchuk turns out to be a real master of ‘soft’ adapting of the religious tradition to the needs of the new ideology.